2018
DOI: 10.18517/ijaseit.8.4.6490
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based Engagement Model for Serious Games

Abstract: Information and Communications Technology (ICT) improve learning quality and increases outcomes while allowing for more natural control of learning systems. It has a significant impact on the economy in many regions. However, there is a lack of female engagement in ICT fields in many countries. Serious Games are effective tools for learning, and it can be used to motivate women to study Computer Science. Gender preference factors affect engagement and motivation to play certain types of digital games, but few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…All the above is done to stimulate skills according to the SG purpose. References: [1,10,26,[28][29][30][31][32][33][34][35][36].…”
Section: Serious Layermentioning
confidence: 99%
See 1 more Smart Citation
“…All the above is done to stimulate skills according to the SG purpose. References: [1,10,26,[28][29][30][31][32][33][34][35][36].…”
Section: Serious Layermentioning
confidence: 99%
“…It must allow interest, immersion, and concentration in the player. References: [1,26,[28][29][30][31][32][33][34][35][36][37]40,41,[43][44][45][46][47][48][49][50].…”
Section: User Experience Layermentioning
confidence: 99%
“…According to a study conducted by Alserri et al [10], who analyzed secondary schools data on the subject, girls who were heavy gamers at 13-14 years old seemed to be more likely to pursue a STEM degree. Therefore he suggested that games could be a way to motivate girls into computer science and STEM degrees in general.…”
Section: Learning To Code Using Serious Gamesmentioning
confidence: 99%
“…A study conducted by Carmichael [16] showcased the beneficial outcomes of combining computer science concepts with video games specifically to a young female target-group. When choosing the coding creation software the educators should consider the following series of requirements: the academic year of the students, the familiarity of the instructor(s) with coding projects, the capability of the student in creating a coding project, and the amount of time students will be spending learning the know-how to do it Alserri et al [10] have developed a conceptual model for gender-based engagement through the use of games, consisting of five elements: 1) Learning elements: these are the elements that distinguish entertainment games from educational games;…”
Section: B Examples Of Serious Games For Learning How To Codementioning
confidence: 99%